Bis(μ-3-hydroxybenzoato-κ3O,O′:O)bis[aqua(3-hydroxybenzoato-κ2O,O′)(1,10-phenanthroline-κ2N,N′)lead(II)] monohydrate - Xiao-Peng Xuan; Pei-Zheng Zhao; Shu-Xia Zhang (Acta Crystallographica Section E, 2008)
In the centrosymmetric binuclear title complex, [Pb2(C7H5O3)4(C12H8N2)2(H2O)2]·H2O, each Pb atom is eight-coordinated in a PbO6N2 environment by two N atoms from the 1,10-phenanthroline (phen) ligand, five carboxylate O atoms from four 3-hydroxybenzoate anions and one O atom from the coordinated water molecule in a distorted bicapped trigonal-prismatic geometry. The benzoate groups coordinate each PbII atom in two different ways. Two benzoate ions behave as bidentate ligands to the Pb atom, and another benzoate ion bridges the Pb atoms, forming a binuclear structure. The dimeric units are packed via O—H...O hydrogen bonds and π–π interactions between the aromatic rings of neighboring molecules, with centroid–centroid distances of 3.552 (2) and 3.641 (2) Å.